Abundance of Collembola in Biopore Infiltration Holes Filled with Organic Waste and Animal Waste - Ganjari, Leo Eladisa; Nugroho, Christianto Adhy (UNIVERSITAS PGRI MADIUN, 2024)
Garbage and flooding are environmental problems that need attention. One solution to dealing with organic waste and flooding is the creation of biopore absorption holes (LRB). Organic waste can be processed into compost with the help of soil animals such as Collembola. The number of soil animals (Collembola) in the biopore hole is influenced by the type of waste used to fill the hole. The aim of this research was to determine the abundance of Collembola in LRBs containing organic waste and animal waste. Used 9 LRBs made from perforated pralon material. LRB group A which contains organic waste only (3 LRB), LRB B which contains organic waste and cow dung (3 LRB) and LRB C which contains organic waste and goat dung (3 LRB). The results of this research show that the LRB composting process has occurred with the help of Collembola. Four types of Collembola were found that were active in biopore infiltration holes (LRB), namely Pseudosinella sp, Ceocobrya sp, Cyphoderus sp and Isotoma sp. There were differences in the abundance of Collembola in LRB sets containing organic waste and animal waste. The Diversity Index value H' < 1, indicates that species diversity is low.